Production of state, capital, and citizenry: the case of Operation Gatekeeper - Huspek, Michael (Social justice, 2001)
Part of a special issue on immigration and boundary policing in an era of globalization. The writer discusses a multifaceted operation, Gatekeeper, conducted by the U.S. along a 66-mile stretch of its border with Mexico and aimed at preventing illegal immigrants from entering the country. He examines the practices employed by the government to run the operation, how these practices affect those targeted by the scheme, and the responses of those who are targeted. Furthermore, he discusses how these practices affect the workings of the state and its influence on the public and capital.